Strategic Commitment Architecture Under Persistent Market Volatility - Granit Agustina (Manexia: Journal of Business, Management, and Creative Economy, 2025)
Persistent market volatility has transformed competitive environments from episodic disruption to structural ambiguity, intensifying the risks associated with irreversible strategic commitments. While existing research emphasizes dynamic capabilities, governance oversight, and organizational learning as mechanisms for navigating turbulence, comparatively limited attention has been devoted to how commitments themselves are architected ex ante. This article develops a theory of strategic commitment architecture to explain how firms structure commitment intensity, escalation thresholds, reversibility capacity, and embedded optionality under persistent volatility. We argue that volatility does not directly generate instability; rather, its destabilizing effects are moderated by the architectural configuration of commitments. Highly concentrated intensity, ambiguous continuation thresholds, low reversibility, and absent optionality amplify escalation traps and reactive oscillation. Conversely, calibrated intensity, explicit thresholds, preserved reversibility, and embedded optionality attenuate volatility transmission and enable disciplined recalibration. By integrating insights from strategic commitment theory, escalation research, and uncertainty management, the framework introduces commitment architecture as a structural moderator of stability under sustained turbulence. The study advances strategy scholarship by reframing commitment as systemic configuration rather than discrete strategic act and outlines avenues for empirical examination across industries.